Effects of active area on UV detection by TiO2-sputtered films. (2021) - Sivapatarnkun, Janjira; Aiempanakit, Kamon; Pudwat, Sayan
Abstract: In this work, TiO2 thin films were used as ultraviolet (UV) detector. TiO2 films with thickness of 300 nm were deposited by sputtering on glass. A pair of symmetric silver paste (SP) was used as electrodes. The proposed UV detector light-dependent resistors were changed characteristics under varying active area of the films. The optical absorption, photocurrent, resistance and current–voltage (I-V) for TiO2 sputtered films under UV-ON and UV-OFF were investigated. The absorption edges of TiO2 sputtered films showed in the range of 315–400 nm. The photocurrents for varying active area were measured under UV irradiation and bias voltage of −25 to 25 V. The results showed that the currents increased as bias voltage increase, and I-V curves showed the different slope changing under varying active area. From the I-V curves measurement, the photocurrent of the small active area was significantly higher than the large active area. The photocurrent for the active area of 0.625 and 2.5 cm 2 were 1.65 and 0.85 µA, respectively under bias voltage of 25 V and UV intensity of 193 µW/cm 2 . Under UV intensity of 193 µW/cm 2, the constant resistance of the active area for 0.625 and 2.5 cm 2 were 0.63 and 19.17 MΩ, respectively. While, the constant resistance of active area of 0.625 cm 2 under UV intensity of 43 and 193 µW/cm 2 were 38.97 and 0.63 MΩ, respectively.